SOCIOECONOMIC AND DEMOGRAPHIC FACTORS ASSOCIATED WITH CONDOM USE AMONG FEMALE SEX WORKERS IN MALAYSIA - Cheah, Yong Kang; Suleiman, Anita; Ramly, Mazliza (Malaysian Journal of Public Health Medicine, 2025)
Female sex workers (FSWs) are more likely to acquire HIV when compared with the general female population. One of the effective prevention methods of HIV is use of condoms. However, not all FSWs use condoms with their clients all the time. The objective of the present study is to examine socioeconomic (i.e., income and education) and demographic factors (i.e., age, ethnicity, and marital status) associated with FSWs’ decision to use condoms with their clients. Secondary data from a large nationwide survey collected by the Ministry of Health Malaysia (n = 630) were used to draw inferences. A logit model was applied to provide important insights into socioeconomic and demographic differences in the odds of using condoms. Results showed that about one-sixth of FSWs (16.5%) did not use condoms with their recent clients. Older FSWs (30–39 years) were more likely to use condoms than younger FSWs (?29 years). Income was correlated with an increased tendency to use condoms. Surprisingly, better educated FSWs were found to have a lower likelihood of using condoms than their less educated counterparts. Compared to Malays, Indians were more likely to use condoms whereas those of other ethnic groups were less likely to use. Findings of the present study lead to a conclusion that age, income, education and ethnicity are explanatory factors of condom use among FSWs in Malaysia. Population-based HIV prevention measures that promote condom use need to pay special attention to FSWs who have a low likelihood of using condoms.